Implikasi Tugas dan Kewenangan Badan Arbitrase Syari’ah Nasional dalam Penyelesaian Sengketa Ekonomi Syari’ah Pasca Putusan MK No.93/PUU-X/2012 Tahun 2008 tentang Pengujian Konstitusional UU No. 21 Tahun 2008 Tentang Perbankan Syari’ah - Ratna Sofiana (UIN Sunan Kalijaga Yogyakarta, 2014)
This paper is intended to examine the proliferation of economic dispute resolutionShari'ah after amendment to the Constitution 1945. Before the change, the ReligiousCourts (PA) as the top judicary are authorized to settle disputes Shariah economy.Now, the judiciary as an institution of Shariah economic dispute resolution experienceproliferation, because the General Court entitled to handle economic disputes Shari'ahunder Article 55 paragraph (2) of Law No. 21 of 2008 concerning Islamic Banking.Due to the proliferation of a completion of economic disputes Shari'ah raises choice offorum which in the case of the same substance, the same object, then given the freedom tochoose, so that will give rise to legal disorder (chaos law). In addition, the decision wouldlead to disparities, are also likely to occur strangeness, because maybe when sentenceborn of religious courts, while the verdict b born of a general court for the same case, orthere are two cases that have similar or even the same same, there will be oddity for theparty receiving.